Tantangan dan Peluang Guru dalam Mengatasi Kemalasan Belajar Siswa di Era Digital - Fatekhah, Khoiril; Rahmawati, Dini; Handayani, Arri (Medan Resource Center, 2024)
This article examines the challenges and opportunities faced by teachers in addressing student laziness in the digital era. Technological advancements have significantly altered how students access information and learn, but they have also introduced issues such as increased distraction from applications and social media. This research identifies key challenges, including technological distractions, decreased learning motivation, and dependence on AI-based technology. Conversely, it highlights opportunities for teachers to develop flexible and engaging digital teaching materials, access diverse learning resources, and innovate teaching strategies. The study emphasizes the need for comprehensive and continuous training programs to enhance teachers' technological and pedagogical skills, ensuring their readiness to tackle digital era challenges. Additionally, it underscores the importance of parental involvement in supporting children's learning at home. By addressing these challenges and leveraging the opportunities, teachers can better motivate students and foster a productive learning environment in the digital age.